PENGARUH IMPLEMENTASI SOP DAN ROLE PLAY TERHADAP KOMUNIKASI SBAR SAAT HANDOVER DI RUANG RAWAT INAP RUMAH SAKIT PEMERINTAH - fitrianola rezkiki (Universitas Fort De Kock, 2022)
The implementation of SBAR communication during handovers in the inpatient room is one of the factors that affect the quality of nursing services. The implementation of SBAR communication during handovers has been running, but not all nurses are able to carry it out properly according to SOPs, so further research is needed on the effect of implementing SOPs and role play on SBAR communication during handover in the inpatient room. This study used a quantitative research design with a quasi-experimental one group pre-post test design, in mid-April 2022. The sample of this study was 12 nurses who were introduced to SBAR communication SOPs during handovers and immediately practiced (role play) in the inpatient room with close observations. carried out for 6 days. The data were analyzed using a dependent t-test to determine the effect of SOP implementation and SBAR communication role play during handover. The results of this study have a p-value of 0.001 which means that there is a significant effect of the application of SOP and role play on the implementation of SBAR communication during handovers in the inpatient room. It is hoped that nursing management can continue to improve supervision to monitor the implementation of nurse SBAR communication in each inpatient room, and immediately issue a written policy regarding SBAR communication SOPs during handovers so that all nurses have the same reference and perception regarding nurses' SBAR communication steps during handovers.